1998
DOI: 10.1016/s0049-0172(98)80001-2
|View full text |Cite
|
Sign up to set email alerts
|

Behçet's Disease

Abstract: BD is a widespread vasculitis affecting young people and involving concurrently or consecutively nearly all organs and systems. Treatment results in better prognosis even when vital organs are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
224
1
17

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(251 citation statements)
references
References 0 publications
7
224
1
17
Order By: Relevance
“…In a hospital-based series, KuralSeyahi et al (7) observed an increased mortality in patients with BD, in particular among young males, which tended to decrease with the passage of time. However, in agreement with our data, 2 other studies reported no increase in mortality in patients with BD (42,43). Turning to morbidity, we looked specifically at inflammatory ocular disease, because this is both a frequent and a potentially serious complication of BD with a significant risk of visual loss (1,2).…”
Section: Seventeen-year Study Of Behçet's Disease In Italysupporting
confidence: 89%
“…In a hospital-based series, KuralSeyahi et al (7) observed an increased mortality in patients with BD, in particular among young males, which tended to decrease with the passage of time. However, in agreement with our data, 2 other studies reported no increase in mortality in patients with BD (42,43). Turning to morbidity, we looked specifically at inflammatory ocular disease, because this is both a frequent and a potentially serious complication of BD with a significant risk of visual loss (1,2).…”
Section: Seventeen-year Study Of Behçet's Disease In Italysupporting
confidence: 89%
“…Its clinical expression may be dominated by orogenital ulcerations, skin lesions, intraocular inflammation and less commonly by arthritic, vascular, gastrointestinal, and neurologic manifestations [1][2][3]. The complete etiology and pathogenesis of BD remain unknown, and the clinical course is characterized by exacerbations and remissions of unpredictable duration and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Behçet's disease (BD) is a chronic inXammatory disorder aVecting various organ systems, characterized by recurrent oral aphthous ulcers, genital ulcers, uveitis, and skin lesions [1,2]. All these common manifestations are self-limiting except for the ocular attacks.…”
Section: Introductionmentioning
confidence: 99%
“…All these common manifestations are self-limiting except for the ocular attacks. Repeated attacks of uveitis can cause blindness [1][2][3]. Involvement of the gastrointestinal tract, central nervous system, and large vessels is less frequent, although it can be life threatening [1,2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%